2017
DOI: 10.1021/acs.jmedchem.7b00010
|View full text |Cite|
|
Sign up to set email alerts
|

Synthetic Approaches to the New Drugs Approved During 2015

Abstract: New drugs introduced to the market every year represent privileged structures for particular biological targets. These new chemical entities (NCEs) provide insight into molecular recognition while serving as leads for designing future new drugs. This annual review describes the most likely process-scale synthetic approaches to 29 new chemical entities (NCEs) that were approved for the first time in 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(56 citation statements)
references
References 144 publications
0
56
0
Order By: Relevance
“…[3,4,6,7] However,t hese solvents are still commonly and widelyu sed in many laboratories because there are no alternatives effective enough for certain reaction cases.E ven in recent industrial processes to make pharmaceuticals,DCM is still occasionally used. [53,54] We therefore studied the application of 4-MeTHPi nr eactions where DCM is typically adopted, specifically,i no xidation, epoxidation, condensation, and olefin metathesis reactions (Scheme 10).…”
Section: Applications Of 4-methp As As Ubstitute For Halogenated Solvmentioning
confidence: 99%
“…[3,4,6,7] However,t hese solvents are still commonly and widelyu sed in many laboratories because there are no alternatives effective enough for certain reaction cases.E ven in recent industrial processes to make pharmaceuticals,DCM is still occasionally used. [53,54] We therefore studied the application of 4-MeTHPi nr eactions where DCM is typically adopted, specifically,i no xidation, epoxidation, condensation, and olefin metathesis reactions (Scheme 10).…”
Section: Applications Of 4-methp As As Ubstitute For Halogenated Solvmentioning
confidence: 99%
“…3 A recent analysis on structures of USFDAapproved drugs administered in combination with other drugs as reported by Njardarson et al revealed that the major importance of these heterocycles in combination drugs is in variety of therapeutic uses. 4 The rich literature [5][6][7][8][9][10][11][12][13][14] on the synthesis of these USFDA-approved drugs is also gaining momentum since for the clinical use of a drug, the drug molecule has be synthesized on a pilot scale using a suitable toolbox of organic chemistry. 15 A plot of the number of publications versus year of publication performed using Sci-Finder 16 for the search string 'synthesis of heterocyclic scaffolds' revealed the increasing popularity of heterocyclic scaffolds synthesized via several organic transformations (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Structure of retaglpitin (184) and antidiabetic drug.Evogliptin: (R)-2,4,5-Trifluorophenylalanine 38b is required for the synthesis of evogliptin (185,Figure 8), an antidiabetic drug in the dipeptidyl peptidase-4 (DPP-4) inhibitor or "gliptin" class of drugs. The South Korean pharmaceutical company Dong-A ST developed evogliptin (185) and it is currently approved for use in South Korea[121][122][123].…”
mentioning
confidence: 99%